Acute Respiratory Distress Syndrome in Severe Brain Injury - Yu. A. Churlyaev; M. Yu. Verein; S. L. Kan; Ye. V. Grigoryev; N. N. Yepifantseva; T. P. Aikina (Общая реаниматология)
Objective: to study the development of acute respiratory distress syndrome (ARDS) in victims with isolated severe brain injury (SBI). Subject and methods. 171 studies were performed in 16 victims with SBI. Their general condition was rated as very critical. The patients were divided into three groups: 1) non-ARDS; 2) Stage 1 ARDS; and 3) Stage 2 ARDS. The indicators of Stages 1 and 2 were assessed in accordance with the classification proposed by V. V. Moroz and A. M. Golubev. Intracranial pressure (ICP), extravascular lung water index, pulmonary vascular permeability, central hemodynamics, oxygenation index, lung anastomosis, the X-ray pattern of the lung and brain (computed tomography), and its function were monitored. Results. The hemispheric cortical level of injury of the brain with function compensation of its stem was predominantly determined in the controls; subcompensation and decompensation were ascertained in the ARDS groups. According to the proposed classification, these patients developed Stages 1 and 2 ARDS. When ARDS developed, there were rises in the level of extravascular lung fluid and pulmonary vascular permeability, a reduction in the oxygenation index (it was 6—12 hours later as compared with them), increases in a lung shunt and ICP; X-ray study revealed bilateral infiltrates in the absence of heart failure in Stage 2 ARDS. The correlation was positive between ICP and extravascular lung water index, and lung vascular permeability index (r>0.4;p<0.05). Conclusion. The studies have indicated that the classification proposed by V. V. Moroz and A. M. Golubev enables an early diagnosis of ARDS. One of its causes is severe brainstem injury that results in increased extravascular fluid in the lung due to its enhanced vascular permeability. The ICP value is a determinant in the diagnosis of secondary brain injuries. Key words: acute respiratory distress syndrome, extravascu-lar lung fluid, pulmonary vascular permeability, brain injury, intracranial pressure.